Thermal conductivity and thermal EMF of nanocrystalline copper sulfides K0,01Cu1,85S and K0,04Cu1,85S - Sakhabayeva, S.M.; Balapanov, M.Kh.; Kuterbekov, K.A.; Giniyatova, Sh.G.; Kubenova, M.M.; Palymbetov, R.Sh.; Ishembetov, R.H. (Recent Contributions to Physics, 2021)
Utilization of the thermoelectric materials in cooling/heating, converting used heat into electrical energy becomes the crucial phenomenal investigation, which new thermoelectric materials have been discovered every day. Thermoelectric materials often require a description of the electrical conductivity and thermoelectric power of the sample from room temperature to 900 K. This paper is presented the study results in thermal conductivity and heat capacity of nanocrystalline copper sulfides K0.01Cu1.85S and K0.04Cu1.85S at the temperature range between 300 K and 700 K. As well as, this work shows the figures of X-ray phase analysis, differential scanning calorimetry (DSC) and differential thermal analysis of alloys. In the investigated temperature range Zeebeck coefficient α for K0,01Cu1,85S fluctuate all around the period, but the figures for K0.04Cu1.85S increase to reaching a pick of around 1.96 mV/K, before falling to around 0.32 mV/K. For the studied alloys, a strong contrast in electronic conductivity in both components of the alloy was observed and a dramatic decrease in thermal conductivity (from 2.0 to 0.5 W ∙ m−1 ∙ K−1), leading to the very high local peak value of the dimensionless thermoelectric figure of merit ZT = 9.67, which is important for possible technical applications. We compared and analyzed obtained data with previous materials and focused on the estimation of the thermoelectric figure of merit of the nanocrystalline copper sulfides.